THE DEVELOPMENT OF THE MAIN CHARACTER INMITCH ALBOM’S THE FIVE PEOPLE YOU MEET IN HEAVEN - Nugraha, Rio Eka (LANTERN (Journal on English Language, Culture and Literature), 2016)
The Five People You Meet in Heaven is a very unique and interesting novel written by a well-known author and script writer Mitch Albom. This novel tells the story about a journey of a man in his search for the purpose of his existence in the afterlife. The purpose of analysing this novel is to understand theme of the story, setting, and the development of the main character in the story. The result shows that in understanding the meaning of life, we must conceive the concrete importance of sacrifice. Albom is a very good writer in combining two dimension of time in the different world, so the reader can easily picture many places that has been described in the novel